Flying - Jones, Carrie, 1971- (a Tor Teen Book, published by Tom Doherty Associates, LLC, 2016)
Mana has always lived a normal life, albeit with an overprotective mother, until the day she comes home to find the house trashed and an alien in the garage. It turns out her mother is an alien hunter who has absconded with a piece of technology that everyone--human and alien--wants to get their hands on. When her mother's partner shows up and orders Mana to come with him, it may be up to Mana to save her mother--and the world.